Transarterial Chemoembolization Plus Radiofrequency Ablation and Iodine-125 Seed Implantation for Hepatocellular Carcinoma in High-Risk Locations: A Propensity Score-Matched Analysis - Zhang G; Ren Y; Liu J; Cao Y; Xiong F; Liang B; Zheng C; Kan X (Journal of Hepatocellular Carcinoma)
Guilin Zhang,1– 3,* Yanqiao Ren,1– 3,* Jiayun Liu,1– 3 Yanyan Cao,1– 3 Fu Xiong,1– 3 Bin Liang,1– 3 Chuansheng Zheng,1– 3 Xuefeng Kan1– 3 1Department of Radiology, Union Hospital, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, 430022, People’s Republic of China; 2Hubei Provincial Clinical Research Center for Precision Radiology & Interventional Medicine, Wuhan, 430022, People’s Republic of China; 3Hubei Province Key Laboratory of Molecular Imaging, Wuhan, 430022, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xuefeng Kan; Chuansheng Zheng, Department of Radiology, Union Hospital, Tongji Medical College, Huazhong University of Science and Technology, No. 1277 Jiefang Avenue, Wuhan, Hubei province, 430022, People’s Republic of China, Email xkliulang1314@163.com; hqzcsxh@sina.comBackground & Aims: The effect of transarterial chemoembolization (TACE) plus radiofrequency ablation (RFA) (TACE-RFA) for hepatocellular carcinoma (HCC) in high-risk locations is not satisfactory. The aim of this study was to compare the clinical outcomes of TACE-RFA plus iodine-125 (125I) seed implantation (TACE-RFA-125I) therapy with those of TACE-RFA for unresectable HCC (≤ 5 cm) in high-risk locations.Methods: From January 2010 to June 2023, the clinical data of 126 patients with unresectable HCC (≤ 5 cm) in high-risk locations who received TACE-RFA-125I or TACE-RFA treatment were retrospectively analyzed. The clinical outcomes between the two groups were compared after propensity score matching (PSM) analysis.Results: Forty-six pairs of patients were matched. The local progression-free survival rates at 1-, 2-, 3-, 4-, and 5-years were 100%, 82.4%, 74.8%, 63.5%, and 54% in the TACE-RFA-125I group, which were significantly higher than 91.3%, 69.4%, 50.7%, 29.4%, and 26.7% in the TACE-RFA group, respectively (p = 0.004). The median progression-free survival in the TACE-RFA-125I group was significantly longer than that in the TACE-RFA group (p = 0.002). The overall survival rates at 1-, 2-, 3-, 4-, and 5-years were 100%, 93.4%, 80.7%, 74.9%, and 64.7% in the TACE-RFA-125I group, which were significantly higher than 97.8%, 78%, 68.6%, 51.1%, and 45.3% in the TACE-RFA group, respectively (p = 0.011). There was no occurrence of major complications or procedure-related deaths in the two groups.Conclusion: Compared with the TACE-RFA treatment, TACE-RFA-125I should be a more effective treatment strategy for patients with unresectable HCC (≤ 5 cm) in high-risk locations.Keywords: radiofrequency ablation, transarterial chemoembolization, iodine-125 seed, hepatocellular carcinoma, high-risk locations